(untitled) (Ameghiniana, 2013)
Thyrsopteris antiqua sp. nov. is described frorn the Upper Cretaceous (Maestrichtian) cf Cerro Cuido, Southern Chile. The morphological characters of the fronds and fructification are verv close to the living monotypic genus Thyrsopteris, endemic of the Juan Fernandez Island.